Modeling the conversion between specific IgE test platforms for nut allergens in children and adolescents. Issue 3 (16th August 2020) - Hoang, Jennifer A.; Celik, Alper; Lupinek, Christian; Valenta, Rudolf; Duan, Lucy; Dai, Ruixue; Brydges, May G.; Dubeau, Aimée; Lépine, Claire; Wong, Samantha; Alexanian‐Farr, Mara; Magder, Ahuva; et al.
Abstract: Background: Multiplex tests allow for measurement of allergen‐specific IgE responses to multiple extracts and molecular allergens and have several advantages for large cohort studies. Due to significant methodological differences, test systems are difficult to integrate in meta‐analyses/systematic reviews since there is a lack of datasets with direct comparison. We aimed to create models for statistical integration of allergen‐specific IgE to peanut/tree nut allergens from three IgE test platforms. Methods: Plasma from Canadian and Austrian children/adolescents with peanut/tree nut sensitization and a cohort of sensitized, high‐risk, pre‐school asthmatics (total n = 166) were measured with three R&D multiplex IgE test platforms: Allergy Explorer version 1 (ALEX) (Macro Array Dx), MeDALL‐chip (Mechanisms of Development of Allergy) (Thermo Fisher), and EUROLINE (EUROIMMUN). Skin prick test (n = 51) and ImmunoCAP (Thermo Fisher) (n = 62) results for extracts were available in a subset. Regression models (Multivariate Adaptive Regression Splines, local polynomial regression) were applied if >30% of samples were positive to the allergen. Intra‐test correlations between PR‐10 and nsLTP allergens were assessed. Results: Using two regression methods, we demonstrated the ability to model allergen‐specific relationships with acceptable measures of fit ( r 2  = 94%‐56%) for peanut and tree nut sIgE testing at the extract and molecular‐level, in order from highest to lowest: Ara h 2, Ara h 6, Jug r 1, Ana o 3, Ara h 1, Jug r 2, and Cor a 9. Conclusion: Our models support the notion that quantitative conversion is possible between sIgE multiplex platforms for extracts and molecular allergens and may provide options to aggregate data for future meta‐analysis. Abstract : This is the first study to present conversion models for specific IgE measurements between three multiplex platforms: Allergy Explorer version 1 (ALEX‐1), mechanisms of Development of Allergy‐chip (MeDALL‐chip), and EUROLINE. Peanut and tree nut‐specific IgE data from the different platforms were modeled with high measures of fit (63%‐94%) for major nut allergens. These conversion models are intended to facilitate harmonization of sIgE data for meta‐analyses upon further validation. Abbreviations: ALEX‐1, Allergy Explorer version 1; MeDALL‐chip, Mechanisms of Development of Allergy‐chip.